United in Fight against prOstate cancer (UFO) registry: first results from a large, multi‐centre, prospective, longitudinal cohort study of advanced prostate cancer in Asia. (30th January 2020) - Uemura, Hirotsugu; Ye, Dingwei; Kanesvaran, Ravindran; Chiong, Edmund; Lojanapiwat, Bannakij; Pu, Yeong‐Shiau; Rawal, Sudhir Kumar; Abdul Razack, Azad Hassan; Zeng, Hao; Chung, Byung Ha; Md Yusoff, Noor Ashani; Ohyama, Chikara; et al.
Abstract : Objectives: To document the management of advanced prostate cancer including diagnosis, prognosis, treatment, and care, in real‐world practice in Asia using the United in Fight against prOstate cancer (UFO) registry. Patients and Methods: We established a multi‐national, longitudinal, observational registry of patients with prostate cancer presenting to participating tertiary care hospitals in eight Asian countries. A total of 3636 eligible patients with existing or newly diagnosed high‐risk localised prostate cancer (HRL), non‐metastatic biochemically recurrent prostate cancer (M0), or metastatic prostate cancer (M1), were consecutively enrolled and are being followed‐up for 5 years. Patient history, demographic and disease characteristics, treatment and treatment decisions, were collected at first prostate cancer diagnosis and at enrolment. Patient‐reported quality of life was prospectively assessed using the European Quality of Life‐five Dimensions, five Levels (EQ‐5D‐5L) and Functional Assessment of Cancer Therapy for Prostate Cancer questionnaires. In the present study, we report the first interim analysis of 2063 patients enrolled from study start (15 September 2015) until 18 May 2017. Results: Of the 2063 enrolled patients, 357 (17%), 378 (19%), and 1328 (64%) had HRL, M0 or M1 prostate cancer, respectively. The mean age at first diagnosis was similar in each group, 56% of all patients had extracapsular extension of their tumour, 28% had regional lymph node metastasis, and 53% had distant metastases. At enrolment, 62% of patients had at least one co‐morbidity (mainly cardiovascular disease or diabetes), 91.8% of M1 patients had an Eastern Cooperative Oncology Group performance score of <2 and the mean EQ‐5D‐5L visual analogue score was 74.6–79.6 across cohorts. Treatment of M1 patients was primarily with combined androgen blockade (58%) or androgen‐deprivation therapy (either orchidectomy or luteinising hormone‐releasing hormone analogues) (32%). Decisions to start therapy were mainly driven by treatment guidelines and disease progression. Decision to discontinue therapy was most often due to disease progression (hormonal drug therapy) or completion of therapy (chemotherapy). Conclusion: In the UFO registry of advanced prostate cancer in Asia, regional differences exist in prostate cancer treatment patterns that will be explored more deeply during the follow‐up period; prospective follow‐up is ongoing. The UFO registry will provide valuable descriptive data on current disease characteristics and treatment landscape amongst patients with prostate cancer in Asia.